Perancangan Blueprint SI/TI Menggunakan TOGAF ADM 9.2 pada KSP Pratama Surya Makmur Mojokerto - Nugraha, Bintang Rassya; Istiyanto, Noerma Pudji; Prayoga, Riza Akhsani Setyo (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
The aim of this research is to improve the efficiency of information management and support the company's vision and mission. The main problems faced by the company are discrepancies in calculations and inaccuracies in attendance within the operational application, as well as a lack of digital platforms such as an official website and adequate social media. The company's manual management also leads to inefficient management and a high potential for errors, which hinders the company's performance and growth. Therefore, a Blueprint for Information/Technology Systems (IT/IS) was designed using TOGAF ADM 9.2. This research employs qualitative methods through observation and interviews. The result is a comprehensive IT/IS Blueprint and an implementation roadmap for the next four years. This Blueprint is expected to guide the development of IT/IS, increase competitiveness, and support the company's business sustainability effectively and efficiently.